Design and Analysis of a Hydraulic Scissor Lift Trolley. - Katwesigye, Wilfred (Kabale University, 2024)
This project focused on designing and analyzing a hydraulic scissor trolley to address the safety hazards and inefficiencies associated with manually handling heavy food sacks in warehouses and food stores. Current practices often involve workers climbing trailers using makeshift wooden stairs without guardrails, creating serious risks of falls and injuries. To improve safety and efficiency, the hydraulic scissor trolley offers a secure and ergonomic solution that minimizes injury risks while boosting worker productivity and operational flow. Powered by hydraulic fluid that drives a cylinder, the scissor lift allows for vertical movement of the platform. This project provides a comprehensive overview of essential components, such as hydraulic cylinders, scissor arms, and the base structure. Materials were selected for optimal durability and strength to withstand operational demands. Engineering sketches detail component dimensions, supported by static stress analysis performed using advanced software like Ansys and SolidWorks. The analysis includes calculations for lift height and additional lifting range, illustrating how this innovative design enhances safety and optimizes material handling in food storage facilities. By implementing this solution, the project aims to reduce delays and bottlenecks, thereby increasing overall productivity in warehouse operations.